2017
DOI: 10.1007/s11277-017-4261-9
|View full text |Cite
|
Sign up to set email alerts
|

A Secure and Efficient Key Authentication using Bilinear Pairing for NFC Mobile Payment Service

Abstract: Near Field Communication (NFC) is widely used as a contactless communication technology in mobile phones for mobile payments. However, achieving payment security is challenging due to the authentication between the NFC-enabled mobile phone users and the merchants. Attackers can use the vulnerabilities of card payment transactions to compromise the NFC communication message and then transmit the wrong payment information to the communicators. An efficiency key authentication scheme is proposed to help NFC-enabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…A habit is also defined as the automatic association of specific clues and actions that are formed by memory through a certain amount of repetitive learning or practice [51], [86]. Wood and Neal [95] suggested that habits develop as people react repeatedly. Nilsen et al, [63] showed that habits are formed by an already repeated behavior.…”
Section: Habit Theoriesmentioning
confidence: 99%
“…A habit is also defined as the automatic association of specific clues and actions that are formed by memory through a certain amount of repetitive learning or practice [51], [86]. Wood and Neal [95] suggested that habits develop as people react repeatedly. Nilsen et al, [63] showed that habits are formed by an already repeated behavior.…”
Section: Habit Theoriesmentioning
confidence: 99%
“…As shown in Table 3, most of the m-banking research focused on user authentication (Apostolopoulos et al, 2013; Barkadehi et al, 2018; Khattak et al, 2021; Parker et al, 2015; Sinigaglia et al, 2020; Y. Wang et al, 2016; Zimmermann & Gerber, 2020) due to rise in an online scam to highlight the challenges connected to the present “authentication schemes,” while others proposed a framework for m-banking verification (Abo-Zahhad et al, 2014; Aithal, 2015; Alhothaily et al, 2018; Basar et al, 2019; Chen et al, 2017; Karim et al, 2020; Nagaraju & Parthiban, 2015; Soviany et al, 2016; Thomas & Goudar, 2018). Similarly, some of the included articles examined m-banking safety and secrecy in general (Cavus et al, 2021; Laukkanen, 2016; Liao et al, 2020; Malaquias & Hwang, 2016, 2019; Mensah et al, 2019; Sharma & Sharma, 2019; Tandon et al, 2018; Thakur & Srivastava, 2015; Y.…”
Section: Resultsmentioning
confidence: 99%
“…However, their scheme consumes more energy consumption 32 . Of late, bilinear pairings 33 have been used for the design of lightweight authentication protocol. Unfortunately, the operations related to bilinear pairing are computationally expensive and more time‐consuming for IoT device communication.…”
Section: Research Backgroundmentioning
confidence: 99%
“…However, their scheme consumes more energy consumption. 32 Of late, bilinear pairings 33 have been used for the design of lightweight authentication protocol.…”
Section: Related Workmentioning
confidence: 99%